2014
DOI: 10.1590/s0100-69162014000400009
|View full text |Cite
|
Sign up to set email alerts
|

Outlining precision boundaries among areas with different variability standards using magnetic susceptibility and geomorphic surfaces

Abstract: ABSTRACT:There is an increasing demand for detailed maps that represent in a simplified way the knowledge of the variability of a particular area or region maps. The objective was to outline precision boundaries among areas with different accuracy variability standards using magnetic susceptibility and geomorphic surfaces. The study was conducted in an area of 110 ha, which identified three compartment landscapes based on the geomorphic surfaces model. To determinate pH, organic matter, phosphorus, potassium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
1
15
1
4
Order By: Relevance
“…The reflections were most marked in the 0.30-0.60 m layer, comprising the most stable pedogenetic soil horizons, but some peaks in the surface layer coincided with the peaks of the deepest layer. Findings of Matias et al (2014), based on the same MS analysis procedure, indicated more pronounced peaks in the 0.30-0.80 m layer. The identification of the limits of landscape compartments was validated by the peaks of the SMW analysis.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The reflections were most marked in the 0.30-0.60 m layer, comprising the most stable pedogenetic soil horizons, but some peaks in the surface layer coincided with the peaks of the deepest layer. Findings of Matias et al (2014), based on the same MS analysis procedure, indicated more pronounced peaks in the 0.30-0.80 m layer. The identification of the limits of landscape compartments was validated by the peaks of the SMW analysis.…”
Section: Resultsmentioning
confidence: 86%
“…In tropical soils, MS has been used to indicate the relationship between landscape and iron oxides, considered indicators of the factors and processes of soil formation Matias et al, 2014Matias et al, , 2015. For being directly related with iron oxides, MS is a covariate of soil mineralogical properties and consequently of different pedogenetic environments, here called landscape compartments (relief).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties considered biological indicators of soil quality are microbial biomass, breathing and nitrogen biological fixation; as chemical indicators, there are pH, organic carbon, effective CEC, N, P, K, Ca, Mg, and electrical conductivity (DIÓGENES et al, 2013;MATIAS et al, 2014). As physical indicators: soil density, soil resistance to penetration, porosity, and aggregate stability (REYNOLDS et al, 2009;IMAZ et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic signature has been used for mineral quali-quantitative analysis in tropical soils (BAHIA et al, 2015), as indicator of environmental quality for CO 2 emissions (BARRIOS et al, 2012;LEAL et al, 2015), identifying distinct landscapes or land boundaries (MATIAS et al, 2014) and areas of potential erosion (SANTOS et al, 2011).…”
Section: Introductionmentioning
confidence: 99%